On the relationship between gingival biotypes and gingival thickness in young Caucasians. Issue 8 (1st March 2014) - Fischer, Kai R.; Richter, Timo; Kebschull, Moritz; Petersen, Nicole; Fickl, Stefan
Abstract Objectives To evaluate a possible relationship between gingival biotypes and gingival thickness, papilla height and gingival width. Material and methods Thirty‐six adult subjects were stratified by their gingival biotype (GB), as defined by transparency of a periodontal probe through the buccal gingival margin, into "thin" (18 subjects) and "thick" (18 subjects) GB. Out of these, extreme cases (6 "very thin", 6 "very thick") were identified. Four different parameters were assessed: gingival thickness (GT), papilla height (PH), probing depth (PD) and gingival width (GW). Results When comparing "thin" and "thick" GB, midfacial GT (0.40 ± 0.07 vs. 0.72 ± 0.11 mm; P < 0.0001), PH (3.76 ± 0.50 vs. 3.95 ± 0.41 mm, P = 0.02) and GW (3.01 ± 1.26 vs. 4.63 ± 0.86 mm, P = 0.04) were lower in the "thin" GB group. Further stratification into moderately and extremely "thin"/"thick" GB eliminated the differences between the moderate groups. Conclusion Our data support the traditional hypothesis that two different gingival biotypes with concomitant properties distinguishable by gingival transparency exist. In addition, we provide evidence that an alternative classification into "very thick", "moderate" and "very thin" biotypes might be advantageous, because the unique properties were seemingly primarily driven by subjects with extreme values.